Penggunaan Gadget: Dampaknya terhadap Interaksi Sosial, Kedisiplinan, dan Desain Pembelajaran Mahasiswa - Ratu Ajeng Galuh Pitaloka; Revi Aulia Putri; Gusmaneli Gusmaneli (CV. ITTC INDONESIA, 2025)
The rapid development of digital technology has made gadgets an integral part of modern life, especially among students. Gadget use in education has both positive and negative impacts. On the one hand, gadgets also facilitate access to education, such as facilitating learning resources, improving communication with friends and family, and supporting student engagement in completing assignments. However, excessive use can reduce the intensity of social interaction and weaken learning discipline. This study aims to determine the effect of gadget use on social interaction and learning discipline among students. Data was obtained from interviews, journals, articles, and books discussing the impact of gadget use. Students who are able to use gadgets effectively are able to balance social interaction and learning discipline, while students who use gadgets excessively experience decreased social sensitivity and time management. Therefore, selfawareness and selfcontrol are needed to maintain appropriate use and avoid excess.